Contribution Of Arm Muscle Power And Confidence Towards Smash Results Of PB Players Reality - Insanul Sobri Wal Afif; Ahmad Rahmadani (CV. AFDIFAL MAJU BERKAH, 2024)
Objective from study this is for know contribution muscle power arms and believe self to results badminton smash PB player Reality. As for types study This is correlation double. Population and sample in study This is PB player. The reality is that there are 15 people with technique taking sample that is total sampling so that samples in research This totaling 15 people. Instrument research used​ is test medicine ball throw, charging questionnaire believe yourself and test smash badminton. Data analysis techniques used is count mark correlation double . Based on results study can concluded that (1) There is contribution power muscle arm to results smash badminton PB player. Reality is 49.56%, (2) Exists contribution believe self to results smash badminton PB player. Reality is 42.12%, (3) Exists contribution power muscle arms and believe self to results smash badminton PB player The reality is 58.37%.